The Needs of Public Health Mitigation as The Impact of Earthquake Disasters in North Sulawesi Region, Indonesia - Lamonge, Annastasia S. Lamonge; Polii, Grace B; Laka, Angela A. M. L; Simanjuntak, Andrean V. H.; Tangkulung, Glatio G; Timbuleng, Jesicca V. D; Anggriani, Theresia; Lewi Ristiyono (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
North Sulawesi is located on a megathrust system and is very vulnerable to destructive earthquake events. Therefore, disaster mitigation from a health perspective must be carried out. Good knowledge will shape a positive attitude as a response that will determine actions in providing effective and optimal health services during a disaster. However, so far, the level of knowledge, attitudes, and actions of doctors in community health centers in North Sulawesi in facing disasters has never been evaluated, so the readiness of doctors in community health centers in facing disasters is still not well understood. One of the effects after a disaster is kidney failure (CKD) due to the lack of fluids needed by the body, making it one of the unavoidable effects of a disaster. Chronic Kidney Disease (CKD) is one of the diseases whose number and prevalence are significant both globally, nationally, and locally in North Sulawesi. The purpose of this research is to: 1) explore the perceptions and experiences of the community regarding the risk factors for CKD, 2) develop and test the effectiveness of a disaster-based education program in increasing community knowledge about CKD prevention. The design used is a multistage mixed method. The research began with the collection of qualitative data through in-depth interviews, followed by the development of an educational program and the experimental testing of the educational program. This research was conducted in Kuwil Village, North Minahasa Regency. A total of 15 participants were involved in the interviews and 38 participants in the experimental phase. Qualitative data is analyzed thematically, while quantitative data is analyzed descriptively through comparison. The results of the qualitative analysis yielded 2 themes. The first theme is the disparity in public knowledge about CKD, and the second theme is the public's efficacy regarding the prevention and impact of CKD. The analysis results using the paired t-test obtained a p-value of 0.000, which means that the disaster-based education program is effective in increasing public knowledge about CKD and its prevention. Having sufficient knowledge and adequate sources of information can help the community in making healthy lifestyle choices, especially in preventing the occurrence of CKD. Disaster-based education programs can be one of the approaches that community health centers can take to improve public literacy regarding CKD prevention.